Red dragon fruit peel as a natural pigment enhancer in goldfish (Carassius auratus) - DAHLIA DAHLIA; ARDIANSYAH ARDIANSYAH; AMRULLAH AMRULLAH; KHUSNUL KHATIMAH; IFHAN DWINHOVEN; DIAN ASRI UNGA MEGA (Smujo International, 2025)
Abstract. Dahlia, Ardiansyah, Amrullah, Khatimah K, Dwinhoven I, Mega DAU. 2025. Red dragon fruit peel as a natural pigment enhancer in goldfish (Carassius auratus). Asian J Agric 9: 777-786. Color quality enhancement is an important factor in the ornamental fish industry, particularly for goldfish (Carassius auratus), as it directly affects market value and consumer preference. The use of carotenoid-based feed additives offers a sustainable alternative for improving the visual appearance of fish. Red dragon fruit (Hylocereus polyrhizus) peel, which is generally discarded as agro-industrial waste, is known to contain natural carotenoids, particularly betacyanin and beta-carotene, which have potential applications in aquaculture. This study aimed to evaluate the effectiveness of Red Dragon Fruit Peel Extract (RDFPE) in improving the color brightness of goldfish, along with related physiological parameters. A completely randomized design was used, consisting of five RDFPE dosage treatments (0, 50, 100, 150, and 200 mL/kg of feed), each with three replicates. The measured parameters included color brightness level, total carotenoid concentration, chromatophore cell count, growth, survival rate, and water quality. The results showed that RDFPE had a significant effect (p<0.05) on color brightness level, with the optimum response observed at 150 mL/kg, followed by a decline at higher dosages. In contrast, RDFPE had no significant effect (p>0.05) on growth or survival rate. Total carotenoid concentration and chromatophore cell count were reported descriptively (mean ± SD) without statistical analysis, indicating that differences among treatments for these parameters require further confirmation. Water quality remained within the optimal range. These findings highlight the potential of RDFPE as a natural and eco-friendly feed additive for enhancing ornamental fish coloration while promoting the sustainable utilization of agro-industrial waste.